A numerical investigation of influence of low-plasticity fines in sand on lateral response of piles. Issue 3 (15th March 2020) - Xu, Ling-Yu; Pan, Jing-Min; Xue, Ying-Ying; Cai, Fei
Abstract: Experimental evidence suggests that sands containing non-plastic or low-plasticity fines may show either decreasing or increasing shear strength with increasing fines content in certain situations. Accordingly, the presence of low-plasticity fines can significantly affect the ultimate lateral soil resistance; thus low-plasticity fines can affect the lateral response of piles. In this study, a quantitative method is proposed for determining the effect of low-plasticity fines in sand on the lateral response of piles in sand by combining a strain wedge model and a unified critical state compatible (UCSC) framework. An equivalent granular state parameter is employed in the UCSC framework to define the soil state uniquely in the strain wedge. The proposed quantitative method is incorporated in a finite element program. A series of numerical analyses are performed on a laterally loaded pile embedded in various relative densities of the base (clean) sand, to which various quantities of low-plasticity fines are added. The effect of low-plasticity fines on the lateral response is investigated. Furthermore, the effect of the low-plasticity fines on the response of the strain wedge is discussed.